Determinan Manajemen Keuangan Pribadi Mahasiswa: Peran Fintech Payment, Financial Literacy, dan Financial Behaviour pada Mahasiswa - Ibrahim Ibrahim; Ernita Lailatul Hikmah; Khotim Fadhli (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This study aims to examine the influence of fintech payment, financial literacy, and financial behavior on the personal financial management of students at University KH. A. Wahab Hasbullah. Methodology/approach:  This study employed a quantitative approach. The sample consisted of 97 respondents selected from a population of 2,771 students using Slovin's formula. Data were collected through a Google Forms questionnaire using a Likert scale and analyzed using SPSS 15. The analysis included validity and reliability tests, classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination. Findings:  The results reveal that fintech payment does not significantly affect students' personal financial management (t-value = 1.241 < t-table = 1.661; Sig. = 0.218 > 0.05). Financial literacy also does not have a significant effect on students' personal financial management (t-value = 1.769 > t-table = 1.661; Sig. = 0.080 > 0.05). In contrast, financial behavior has a positive and significant effect on students' personal financial management (t-value = 4.147 > t-table = 1.661; Sig. = 0.000 < 0.05). Simultaneously, fintech payment, financial literacy, and financial behavior significantly influence students' personal financial management (F-value = 48.324 > F-table = 2.703; Sig. = 0.000 < 0.05). Practical implications:  The findings provide practical insights for higher education institutions in designing financial education programs that emphasize the development of positive financial behavior to improve students' personal financial management. Originality/value:  This study provides empirical evidence regarding the simultaneous contribution of fintech payment, financial literacy, and financial behavior in explaining students' personal financial management in Indonesian higher education.